Risk assessment of obstructive sleep apnea syndrome in pediatric patients with vitamin D deficiency: A questionnaire-based study. Issue 39 (September 2016) - Ozgurhan, Gamze; Vehapoglu, Aysel; Vermezoglu, Oznur; Temiz, Rabia Nur; Guney, Asuman; Hacihamdioglu, Bulent
Abstract : Abstract: The aim of the following study is to evaluate the risk of obstructive sleep apnea syndrome (OSAS) in subjects with vitamin D deficiency. Prospective and comparative study. We enrolled 240 subjects into the study. The participants were divided into 2 groups based on 25-hydroxyvitamin D (25[OH]D) levels: low level of 25(OH)D (<20 ng/mL) group (n = 120) and control (>20 ng/mL) group (n = 120). Subjects were classified as being at a high or low risk of developing OSAS by using the Berlin Questionnaire. Risk of developing OSAS, gender, age, and body mass index (BMI) z-score were assessed by comparing the low level of 25(OH)D group and control group. No statistically significant difference was observed between the low level of 25(OH)D group and control group in terms of gender, age, and BMI z-score distributions; P = 0.323, P = 0.387, and P = 0.093, respectively. There were 24 subjects with high risk of developing OSAS in 2 groups (17 subjects in the low level of 25[OH]D group and 7 subjects in the control group). In the low level of 25(OH)D group, the risk of developing OSAS was found to be significantly higher than the control group ( P = 0.030). BMI z-score was found significantly higher in high-risk groups than low-risk groups ( P = 0.034 for low-level 25[OH]D group and P = 0.023 for control group). The findings revealed that low level of 25(OH)D increases the risk of developing OSAS.